Overwater chalet development and land ownership issue from the Islamic perspectives - Mahamod, Lukman Hakim; Wan Yahya, Wan Nur Amirah; Ibrahim, Mansor; Hashim, Khairusy Syakirin Has-Yun; Wan Shamsuddin, Wan Norshafiqah; Othman, Rashidi (2016)
Waterfront as general term can be defined to land that is fronting the water. Some researchers referred waterfront as city port, riverfront, riversides and water edge. It refers to water’s edge of any cities or town either it is river, lake, ocean, bay, creek or canal. A waterfront is the meeting point between land with water, and it gives natural attraction to the people. Among the growing trends in tourism industries which related to waterfront development is overwater chalets. However, some issues are unclear which need to be further explored such as matters related to land ownership granted and limitation for its boundary as these developments may affect the existent recreational area for the public. Therefore, this study aims to seek the best practice for overwater development from the view of Islamic perspective. A qualitative method was used and the results showed there were some criteria that need to be fulfilled in considering overwater development towards shariah compliant. The research will contribute to the major research on Muslim-friendly or shariah compliant of Tourism Accommodation Premises (TAP) in improving the Muslim-Friendly Hospitality Services (MFHS) Malaysian Standard.